## Solving the Equation (m + 3) / 2 = m - 5

This article will guide you through the steps of solving the equation **(m + 3) / 2 = m - 5**.

### Step 1: Multiply Both Sides by 2

To eliminate the fraction, multiply both sides of the equation by 2:

```
2 * [(m + 3) / 2] = 2 * (m - 5)
```

This simplifies to:

```
m + 3 = 2m - 10
```

### Step 2: Isolate the 'm' Term

To isolate the 'm' term on one side of the equation, subtract 'm' from both sides:

```
m + 3 - m = 2m - 10 - m
```

This simplifies to:

```
3 = m - 10
```

### Step 3: Solve for 'm'

Finally, add 10 to both sides to solve for 'm':

```
3 + 10 = m - 10 + 10
```

This simplifies to:

```
m = 13
```

### Solution

Therefore, the solution to the equation (m + 3) / 2 = m - 5 is **m = 13**.